Online banking user interface: Perception and attitude - Ojeniyi, Adegoke; Alo, O. K; Oyetade, E. M; Ang, M. T; Sanusi, Yekinni K. (2015)
Online banking user interface gives customers' the platform to link-up their bank servers and conduct transactions over the Internet.It provides both customers and banks with great opportunities. Security and privacy are one of the big issues that banks are contending with to survive the global competitive banking market.Many technological innovation and solution are being suggested to combat these issues.However, these solutions are making banking user interface more complicated and complex which is affecting the simple and clear natures of an ideal banking user interface.Thus, this paper aim at examining customers' perception and attitude toward the ease of use of online banking interface in Nigeria commercial bank.The study will probe on how advancement on online banking user interface securities feature affect customers' attitude and intention to use the interface.The investigation of this study was done in the light of Technological Acceptance Model (TAM). A survey was carried out on 500 respondents in Nigeria out of which 356 were usable, giving a response rate of 71.2 percent. Data were analyzed by employing descriptive analysis using SPSS.Findings of the study indicates that as banks are providing more security measures on their online banking user interface, similarly attention should be given to ease of use of the interface.Consequently, if banks can ensure that both security and ease of use are integrated on their user interface, customers will have more confidence in adoption and usage of online banking user interfaces without hesitations.